P63 Using fully immersive simulation to identify latent errors in a new critical care unit. (5th November 2017) - Beglinger, S; Ayres, L; Jones, CP
Abstract : Context: Simulation in-situ is now recognised as a method for identifying knowledge gaps, enhancing team cohesion, and importantly revealing latent errors to improve patient safety. 1 We previously used in-situ simulation in our new emergency department. 2 In January 2017, Aintree University Hospital opened a new 24 bed Critical Care Department (CCD), the final phase of a £35  million Urgent Care and Trauma Centre project, serving Cheshire and Merseyside. We designed an in-situ simulation exercise and present the outcomes of this activity. Aims: 1. Test established standardised operating procedures in a new environment and identify latent errors. 2. To orientate staff to locations of emergency and routine equipment. 3. Improve situational awareness and confidence to work on the new unit. Methodology: Members of the multidisciplinary team were released to the new CCD to complete one of eight high fidelity emergency simulation scenarios: * Cardiac arrest * Preparation for Out Of Hospital transfer * Patient self-extubates and pulls out CVC line * Cardiac arrest – trauma patient * Massive GI bleed * Post-op septic shock * Emergency transfer to theatre * Dislodged tracheostomy tube. Prior to simulations, staff received a tour of the unit. Post simulation debriefs were structured using a SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats) and feedback obtained. Outcomes: Unfortunately, due to staffing pressures, only 16 out of a planned 40 staff members could be freed from work activities to complete the exercise. 30 latent errors were identified and categorised as immediate, urgent and delayed problems requiring attention. Ergonomics of the unit were assessed and we noted increased numbers of blind spots, as well as difficulties maintaining staff cross-cover, situational awareness and support for routine and emergency patient care. We highlighted equipment deficiencies, faults and consulted with regards to the ideal equipment locations to improve future economy of movement. This exercise supported requests to employ additional staff to cover each shift. 9 out of the 16 staff members provided feedback and reported improved confidence for locating emergency drugs, specialist equipment, control drugs and clinical documentation. Conclusion: In-situ simulation identified latent risks in our new CCD. Earlier detection ensured many issues could then be rectified prior to patients being admitted. Staff reported improved orientation, preparedness and confidence to work on the new unit. References: . Geis GL, Pio B, Pendergrass TL, Moyer MR, Patterson MD. Simulation to assess the safety of new healthcare teams and new facilities. Simul Healthc 2011;6:125–33. . Jones C, Murphy M, Welfare E, Mercer SJ. Using fully immersive simulation to identify latent errors in a new major Trauma centre. BMJ Journal of Simulation Technology and Enhanced Learning 2015;1(S2):A21.